C-type lectin like-receptor 2 (CLEC-2) signals independently of lipid raft microdomains in platelets - Manne, Bhanu Kanth (Biochem Pharmacol, 2014)
C-type lectin like-receptor 2 (CLEC-2) has been reported to activate platelets through a lipid raft-dependent manner. Secreted ADP potentiates CLEC-2-mediated platelet aggregation. We have investigated whether the decrease in CLEC-2-mediated platelet aggregation, previously reported in platelets with disrupted rafts, is a result of the loss of agonist potentiation by ADP. We disrupted platelet lipid rafts with methyl–β-cyclodextrin (MβCD) and measured signaling events downstream of CLEC-2 activation. Lipid raft disruption decreases platelet aggregation induced by CLEC-2 agonists. The inhibition of platelet aggregation by the disruption of lipid rafts was rescued by the exogenous addition of epinephrine but not 2-Methylthioadenosine diphosphate (2MeSADP), which suggests that lipid raft disruption effects P(2)Y(12)-mediated G(i) activation but not G(z). Phosphorylation of Syk (Y525/526) and PLCγ2 (Y759), were not affected by raft disruption in CLEC-2 agonist-stimulated platelets. Furthermore, tyrosine phosphorylation of the CLEC-2 hemi-ITAM was not effected when MβCD disrupts lipid rafts. Lipid rafts do not directly contribute to CLEC-2 receptor activation in platelets. The effects of disruption of lipid rafts in in vitro assays can be attributed to inhibition of ADP feedback that potentiates CLEC-2 signaling.